Konstruksi Realitas Politik dalam Media Massa (Studi Pesan Politik dalam Media Cetak pada Masa Pemilu 1999) - Hamad, Ibnu (Makara Human Behavior Studies in Asia, 2004)
During the 1999-campaign period generally the mass media in Indonesia constructed political parties like a music group; and present the politicians acts as celebrities. At that time, national newspapers describe political parties as the instrument to harvested masses. Meanwhile the political party functions, as broker within the clearinghouse of ideas in the democratic lives didn’t appear within the political party’s discourse. In spite of the media have different interests one each other in news making the political parties, such as ideological, idealism, political, and economic or market factors.